Pengaruh Motivasi Dan Upah Kerja Terhadap Produktivitas Kerja Karyawan PT. Sumber Alfaria Trijaya Tbk Di Delanggu - Nur Setyanto, Lahan; , Dra. Mabruroh, MM (2016)
Economic growth conditions in the areas of business today is quite high, which can be seen from the growth of companies with similar products, increasing competition for the consumer market. Important issues often faced by the leaders is how to increase the productivity of employees in order to support the successful achievement of objectives. This study aimed to analyze the influence of motivation and wages on work productivity and analyze which is the most dominant variable in making the employee's productivity PT Sumber Alfaria TRIJAYA Tbk. Based on the results of this research can be considered a company to take policy strategies to improve human resources. The sample in this study were employees of PT Sumber Alfaria TRIJAYA Tbk totaling 100 employees. The sampling technique in this research is purposive sampling. Based on the survey results revealed that the motivation variable (X1) and wages (X2) have a significant effect on employee productivity TRIJAYA Tbk PT Sumber Alfaria because thitung> ttable. The results of calculations simultaneously obtained F count> F table, so that the variable motivation and reward work together significant effect on employee productivity PT Sumber Alfaria TRIJAYA Tbk. Variable wages (X2) has the most dominant influence on employee productivity Alfaria Trijaya Resources Tbk, because of variable wages have thitung greater than the motivation variable, that is equal to 4.566. So variable wage the most dominant influence on employee productivity TRIJAYA Tbk PT Sumber Alfaria proven true. Keywords: motivation, wages, labor productivity